Cu-high-entropy carbide composite material and preparation method thereof
Patent Information
- Application Number
- CN202611049018.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-16
AI Technical Summary
然而,多组元体系的固溶反应能垒较高,现有制备方法主要依赖机械合金化或高温固相反应烧结,前者耗时长且易引入污染,后者需在1800℃以上长时间保温、能耗高昂,且上述方法均依赖前期的机械压坯工序以缩小颗粒间距、增加扩散接触面积,这极大限制了高熵碳化物在复杂结构构件中的应用
[0023] This invention directly uses commercially available single-component carbide powder as a precursor, eliminating the need for high-entropy ceramic powder pre-synthesis and significantly reducing raw material costs. At the same time, it couples precursor direct writing molding, in-situ high-entropy sintering, and pressureless infiltration into a continuous process chain, which is much shorter than the traditional multi-step process of "pre-synthesis → powder processing → pressing → sintering → pressure infiltration".
Smart Images

Figure CN122916709A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-entropy ceramic composite material preparation technology, specifically a Cu-high-entropy carbide composite material and its preparation method. Background Technology
[0002] High-entropy carbides (HECs) are single-phase ceramics formed by the near-equimolar solid solution of five or more transition metal elements at the sublattice positions of a rock-salt-type crystal structure. They hold significant promise for applications in aerospace thermal protection, high-end wear-resistant cutting tools, and ultra-high temperature structural ceramics. However, the solid solution reaction barrier of multi-component systems is relatively high. Existing preparation methods mainly rely on mechanical alloying or high-temperature solid-state reaction sintering. The former is time-consuming and prone to introducing contamination, while the latter requires prolonged holding at temperatures above 1800°C, resulting in high energy consumption. Furthermore, both methods rely on the initial mechanical pressing process to reduce particle spacing and increase diffusion contact area, which greatly limits the application of high-entropy carbides in complex structural components.
[0003] In recent years, direct ink writing (DIW) technology has been introduced into the field of high-entropy ceramic component manufacturing. However, most of its existing technical routes directly use pre-synthesized high-entropy ceramic powder to prepare printing paste. The pre-synthesis process is costly and the pre-synthesized powder has low sintering activity. Subsequent densification still requires high temperature and high pressure assistance. What is even more attractive in engineering is to mix low-cost single-component carbide precursor powders to form a slurry for printing, and then complete the high-entropy reaction in situ within the preform. However, the primary difficulty in this approach lies in the slurry preparation stage: the high-entropy carbide system requires the simultaneous use of at least five single-component carbide powders. These powders have significantly different surface chemical properties (e.g., TiC, NbC, and TaC are hydrophilic, while WC and Cr3C2 tend to be hydrophobic). The isoelectric points and surface charge densities of different carbides are also different, which leads to problems such as selective flocculation, component segregation and sedimentation, or uneven solid content after mixing multi-component powders. It is difficult to formulate a uniform and stable slurry that meets the stringent rheological performance requirements of DIW technology (high yield stress under low shear and low viscosity under high shear).
[0004] Having solved the slurry preparation problem, this approach faces a second fundamental challenge: the direct-write forming green body relies on the layer-by-layer stacking of slurry filaments, with particles held together only by organic binders. This lacks the mechanical densification effect of pressing, resulting in high porosity and loose particle contact. Under these conditions, there are few effective diffusion paths and small contact areas between particles. Conventional sintering struggles to overcome the kinetic energy barrier of high-entropy solid solution, leading to either incomplete reactions and residual multiphase phases, or significantly increased temperatures and times to enhance the reaction rate, resulting in severe grain coarsening and skeletal shrinkage deformation. This makes it impossible to simultaneously achieve in-situ high-entropy formation and high-fidelity preservation of the three-dimensional configuration.
[0005] Furthermore, when preparing metal matrix composites by combining high-entropy carbides with metallic copper, most common carbides (such as TiC, ZrC, HfC, etc.) have contact angles with liquid copper that are much greater than 90°, resulting in poor wettability and a lack of thermodynamic conditions to drive pressureless capillary infiltration. Existing processes can only employ pressure infiltration, which is cumbersome, requires expensive equipment, and is difficult to apply to complex three-dimensional configurations. Although some single-component carbides (such as WC, Cr3C2) have some wettability with liquid copper, their high-temperature mechanical properties and ablation resistance are far inferior to those of high-entropy carbides, failing to meet the demands of harsh operating conditions. Therefore, there is an urgent need to develop a preparation method that can couple multi-component precursor slurry preparation, direct writing molding, in-situ high-entropy synthesis, and pressureless copper infiltration into a continuous process chain. Summary of the Invention
[0006] To address the bottlenecks in existing technologies, such as the difficulty in preparing multi-component carbide powder slurry, the difficulty in in-situ high-entropy in loose direct-write preforms, and the need for pressurized infiltration due to poor wettability between carbides and copper, this invention provides a method for preparing Cu-high-entropy carbide composite materials and the composite material obtained by this method.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows:
[0008] A method for preparing a Cu-high-entropy carbide composite material includes the following steps:
[0009] S1: Mix at least five single-component transition metal carbide powders, dispersants, binders and defoamers to prepare a mixed carbide slurry with shear-thinning properties;
[0010] S2: The mixed carbide slurry is printed using a direct ink writing method to obtain a mixed carbide precursor preform;
[0011] S3: The mixed carbide precursor green body is subjected to ultra-fast sintering to cause in-situ solid solution reaction of each component transition metal carbide, resulting in a high-entropy carbide framework with a single-phase face-centered cubic rock salt structure; the heating rate of the ultra-fast sintering is 400-1000℃ / min, the sintering temperature is 1900-2300℃, and the holding time is 1-5min.
[0012] S4: Under vacuum conditions, metallic copper is heated to melt, and the molten copper is infiltrated into the pores of the high-entropy carbide framework through pressureless capillary infiltration. After cooling, Cu-high-entropy carbide composite material is obtained.
[0013] Furthermore, the single-component transition metal carbide powder mentioned in S1 is selected from at least five of TiC, VC, NbC, TaC, Cr3C2, Mo2C and WC, and the FSSS particle size of the powder is 0.2 to 3 μm. The proportion of each carbide powder is weighed according to the equimolar ratio or near equimolar ratio of transition metal atoms.
[0014] Furthermore, the solid volume fraction of the mixed carbide slurry in S1 is 30-50 vol%, the binder accounts for 0.5-5% of the mass of the carbide powder, the binder is polyether F127 or xanthan gum, the dispersant accounts for 0.5-2% of the mass of the carbide powder, and the dispersant is sodium carboxymethyl cellulose.
[0015] Furthermore, the printing parameters for direct ink writing described in S2 are: nozzle orifice diameter 0.2–1.0 mm, layer height 0.15–0.8 mm, printing speed 2–10 mm / s, extrusion pressure 0.1–0.6 MPa, and filling method is linear, concentric circle, or zigzag.
[0016] Furthermore, the ultra-fast high-temperature sintering described in S3 is carried out under vacuum or inert atmosphere. Before heating to the target temperature, the temperature is first raised to 500-700℃ in vacuum at 100-300℃ / min and held for 1-5 minutes for degreasing treatment.
[0017] Furthermore, the average linear shrinkage rate of the high-entropy carbide framework described in S3 is 9.5–12.5%, and the general formula of the high-entropy carbide framework is (A1A2…A…). n C 1-x A1 to A n Each element is independently selected from one of Ti, V, Nb, Ta, Cr, Mo, and W, and any five or more elements coexist in the same metal sublattice, n≥5; x represents the carbon sublattice vacancy concentration, and 0≤x≤0.15.
[0018] Furthermore, the pressureless capillary impregnation temperature described in S4 is 1100–1200℃, the holding time is 3–10 min, and the vacuum degree is ≤1×10⁻⁶. -3 Pa.
[0019] A Cu-high-entropy carbide composite material.
[0020] Furthermore, the composite material is composed of a high-entropy carbide ceramic phase and a metallic copper phase. The high-entropy carbide ceramic phase has a single-phase face-centered cubic rock salt structure with the general formula (A1A2…A…). n C 1-x A1 to A n Each is independently selected from one of Ti, V, Nb, Ta, Cr, Mo, and W, where n ≥ 5 and 0 ≤ x ≤ 0.15.
[0021] Furthermore, the composite material has a density of 99-99.5%, a volume fraction of 20-40% for the high-entropy carbide ceramic phase, and a porosity of less than 1%.
[0022] The present invention has the following beneficial effects:
[0023] This invention directly uses commercially available single-component carbide powder as a precursor, eliminating the need for high-entropy ceramic powder pre-synthesis and significantly reducing raw material costs. At the same time, it couples precursor direct writing molding, in-situ high-entropy sintering, and pressureless infiltration into a continuous process chain, which is much shorter than the traditional multi-step process of "pre-synthesis → powder processing → pressing → sintering → pressure infiltration".
[0024] In existing technologies, direct-write forming of preforms suffers from a lack of mechanical compaction and loose particle contact, making it difficult for conventional sintering to overcome the high-entropy solid solution kinetic energy barrier. This invention employs ultra-fast sintering (heating at 400–1000℃ / min, holding for 1–5 min), which induces numerous non-equilibrium defects at the particle interface to reduce diffusion activation energy. Simultaneously, the extremely short holding time effectively suppresses grain coarsening and framework shrinkage. XRD verification shows that the resulting framework is a single-phase face-centered cubic rock-salt structure with no residual single-component phases; the average linear shrinkage rate of the framework does not exceed 13%, far lower than the over 20% of conventional sintering, achieving high-fidelity preservation of the three-dimensional configuration while ensuring complete high-entropy formation.
[0025] This invention overcomes the technical bottleneck of poor wettability between carbides and copper, achieving pressureless infiltration densification. Traditional carbides (such as TiC, ZrC, and HfC) have a contact angle >90° with liquid copper, requiring pressure infiltration. This invention, through specific component design, reduces the stable contact angle between the high-entropy dissolved carbides and liquid copper to 18–30°, providing sufficient capillary driving force to achieve complete penetration of molten copper into complex three-dimensional frameworks without external pressure. The resulting composite material achieves a density of 99–99.5% and a porosity of less than 1%.
[0026] This invention enables the fabrication of complex, irregularly shaped Cu-high-entropy carbide components. By combining the three-dimensional structural design freedom of direct-write molding with the low shrinkage characteristics (linear shrinkage rate ≤15%) of ultra-fast sintering, this invention can prepare complex, irregularly shaped components that are difficult to achieve using traditional pressing and sintering methods, without requiring extensive subsequent processing. This provides a feasible technical path for complex structural applications in fields such as aerospace thermal protection and high-end wear-resistant components. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the process flow of the preparation method of the present invention;
[0028] Figure 2 The rheological property curves of the mixed carbide slurry in Example 1 are as follows: (a) the relationship between viscosity and shear rate, and (b) the relationship between storage modulus G' and loss modulus G'' with shear stress.
[0029] Figure 3Macroscopic photographs of the products at each stage in Example 1: (a) the mixed carbide precursor preform obtained by direct writing molding, (b) the (Ti) preform synthesized in situ after ultra-fast sintering. 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 1-x (c) Cu-(Ti) obtained after pressureless infiltration, high-entropy carbide framework. 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 1-x Composite materials;
[0030] Figure 4 The X-ray diffraction pattern of the high-entropy carbide framework after ultra-fast sintering at 2000℃ in Example 1 is shown.
[0031] Figure 5 The Ti synthesized in situ by ultra-fast sintering in Example 1 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 1-x Energy-dispersive X-ray spectral elemental distribution of high-entropy carbide frameworks;
[0032] Figure 6 The curves show the contact angle versus time when molten Cu droplets wet three high-entropy ceramic substrates in Examples 1, 3, and 6 (1100°C, vacuum 5×10⁻⁶). -4 Pa);
[0033] Figure 7 The Cu-(Ti) after pressureless impregnation in Example 1 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 1-x Energy dispersive X-ray spectral elemental distribution at the interface between the copper phase and high-entropy carbide in the composite material;
[0034] Figure 8 The X-ray diffraction patterns are those of the high-entropy carbide frameworks prepared in Examples 2-6. Detailed Implementation
[0035] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0036] This invention directly uses commercially available single-component carbide powders as precursors, selecting at least five from TiC, VC, NbC, TaC, Cr3C2, Mo2C, and WC, ensuring the difference factor of unit cell parameters in the system during combination. Keep it as small as possible (empirical value less than 3.25%) to facilitate high entropy formation and wetting optimization. The calculation is shown in formula (1).
[0037]
[0038] In the formula Let be the lattice constant of the carbide corresponding to the i-th component. denoted as the mole fraction of each component, and N as the number of components.
[0039] Example 1 Cu-(Ti) 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 1-x Preparation of composite materials
[0040] S1 slurry preparation:
[0041] TiC, Cr3C2, VC, NbC, and TaC were used as carbide precursor powders, with FSSS particle sizes ranging from 0.2 to 3 μm. Each carbide powder was weighed according to an equimolar ratio of Ti, Cr, V, Nb, and Ta atoms (1:1:1:1:1). The specific formula is as follows: Assuming a total transition metal molar amount of 5 mol (1 mol of each element), then 1 mol of TiC, 1 mol of VC, 1 mol of NbC, 1 mol of TaC, and 1 / 3 mol of Cr3C2 (providing 1 mol of Cr atoms) were weighed. The total molar amount of carbon in the above formula is: 1(TiC) + 1(VC) + 1(NbC) + 1(TaC) + 1 / 3(Cr3C2) = 4.667 mol, and the total molar ratio of carbon to transition metal is 4.667 / 5 = 0.933, meaning the nominal composition of the system is (TiC + Cr3C2) / 5 = 0.933. 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 0.933The carbon sublattice vacancy concentration x≈0.067. Deionized water, polyether F127 (3% of the carbide powder mass), sodium carboxymethyl cellulose (0.5% of the carbide powder mass), and BYK-024 defoamer (0.2% of the carbide powder mass) were mixed and added to a zirconia ball mill jar. The mixture was ball-milled at a ball-to-powder mass ratio of 3:1 and a ball milling speed of 1200 rpm for 1 hour to prepare a mixed carbide slurry with a solid volume fraction of 43 vol%.
[0042] The rheological properties of the obtained slurry are referenced Figure 2 .like Figure 2 As shown in (a), the slurry viscosity decreases monotonically with increasing shear rate, exhibiting typical shear thinning behavior. Figure 2 As shown in (b), in the low shear stress range, the storage modulus G' is significantly greater than the loss modulus G'', and the slurry exhibits an elastic state; when the shear stress exceeds the yield stress, G'' exceeds G', and the slurry transforms into a flowable state. This rheological characteristic of "high elasticity under low shear and easy flow under high shear" is the key to achieving high shape fidelity in direct-write molding.
[0043] S2 direct writing modeling:
[0044] The obtained slurry was loaded into the cartridge of a direct ink writing 3D printer. The printing parameters were: nozzle orifice diameter 0.25 mm, layer height 0.2 mm, printing speed 4 mm / s, extrusion pressure 0.35 MPa, linear filling pattern, and interlayer spacing 0.3 mm. The resulting ceramic layer width was approximately 0.25 mm. After printing, a mixed carbide precursor preform was obtained, and its macroscopic morphology is shown in [reference needed]. Figure 3 (a).
[0045] S3 Ultrafast In-situ High-Entropy Sintering:
[0046] The printed preform was dried in a vacuum drying oven at 70 °C for 8 h. The dried preform was then placed in a self-made ultra-fast sintering apparatus (Journal of the European Ceramic Society, 41(2021) 5768-5773), see below. Figure 1 The equipment used was an ultra-rapid heating and cooling vacuum / atmosphere sintering furnace based on a graphite felt heating element, with an infrared thermometer (temperature range 150-3000 ℃) used to monitor the sample surface temperature in real time. First, the furnace chamber was evacuated to 5.0 Pa, and the temperature was increased to 600 ℃ at 200 ℃ / min and held for 3 min to degrease the organic matter. Then, argon gas was introduced to 0.5 standard atmospheres, and the temperature was increased to 2000 ℃ at 500 ℃ / min and held for 2 min to allow the multi-component carbide precursor to undergo an in-situ solid solution reaction to synthesize high-entropy carbides. After sintering, the temperature was cooled to room temperature at 400 ℃ / min.
[0047] Macroscopic morphology reference of the obtained high-entropy carbide framework Figure 3 (b) Dimensional measurements were taken of the blank skeleton before and after sintering. The linear shrinkage rate was 12.5% in the length direction, 11.8% in the width direction, and 11.5% in the height direction, with an average linear shrinkage rate of approximately 11.9%. As shown in the figure, the skeleton maintained a three-dimensional configuration that was basically consistent with the printed blank.
[0048] Reference Figure 4 X-ray diffraction analysis showed that the sample after ultra-rapid sintering at 2000℃ exhibited only diffraction peaks of a single-phase face-centered cubic rock salt structure, with no diffraction peaks of any single-component carbide residual phase, confirming that the multi-component carbide precursor had been completely dissolved and formed (Ti). 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 1-x Single-phase high-entropy carbides.
[0049] Reference Figure 5 Energy-dispersive X-ray spectroscopy (EDS) elemental distribution analysis showed that Ti, Cr, V, Nb, and Ta were uniformly distributed at the micrometer scale, with no elemental segregation or agglomeration, further verifying the completeness and homogeneity of the high-entropy solid solution reaction. EDS quantitative analysis ( Figure 5 The region shows that the atomic percentages of each transition metal element are: Ti (18.7%), Cr (23.0%), V (20.4%), Nb (17.7%), and Ta (20.1%). No significant evaporation loss of Cr was observed, which is attributed to the effective suppression of Cr evaporation by the Ar protective atmosphere and the extremely short high-temperature holding time (only 2 min).
[0050] S4 Vacuum Pressureless Copper Impregnation:
[0051] The obtained high-entropy carbide framework was placed in a boron nitride crucible and secured at the edges with alumina sheets. A pre-cut copper cylinder (approximately 1.2 times the volume of the ceramic framework) was placed on top of the framework. The crucible was placed in the center of the infiltration furnace heating zone. The mechanical and molecular pumps were started to evacuate the furnace to a vacuum of 1 × 10⁻⁶. -3 Pa. Increase the temperature to 300℃ at 5℃ / min and hold for 10 min; then increase the temperature to 1000℃ at 10℃ / min and hold for 10 min; continue to increase the temperature to 1100℃ at 5℃ / min and hold for 10 min, allowing the copper block to completely melt and spontaneously infiltrate. (Refer to...) Figure 6Cu exhibits excellent wettability with this pentagonal high-entropy substrate. Driven by capillary forces and interfacial wetting, molten copper spontaneously infiltrates into the interconnected pores within the high-entropy carbide framework. After infiltration, the substrate is cooled to room temperature at a rate of 10 °C / min to obtain Cu-(Ti) 0.2 Cr 0.2 V 0.2 Nb 0.2 Ta 0.2 C 1-x Composite materials.
[0052] Macroscopic morphology reference of the obtained composite material Figure 3 (c). Reference Figure 7 Energy-dispersive X-ray spectroscopy (EDS) analysis at the interface between the copper phase and the high-entropy carbide showed good interfacial bonding with no obvious defects, and no reaction product layer formed between the Cu element and the various metal elements in the ceramic framework. Archimedes' method testing revealed a composite material density of 99.3%, confirming that the molten copper had fully filled the interconnected pores of the framework under capillary force, achieving near-complete densification. The volume fraction of the high-entropy carbide ceramic phase in the composite material was approximately 35%, with the remainder being metallic copper.
[0053] Example 2 Cu-(Ti) 0.2 V 0.2 Nb 0.2 Mo 0.2 W 0.2 C 1-x Preparation of composite materials
[0054] S1 slurry preparation:
[0055] TiC, VC, NbC, Mo2C, and WC were used as carbide precursor powders with a FSSS particle size of 0.2–3 μm. Each carbide powder was weighed according to an equimolar ratio of Ti, V, Nb, Mo, and W atoms (1:1:1:1:1). The specific formula is as follows: Assuming a total transition metal molar amount of 5 mol (1 mol of each element), then 1 mol of TiC, 1 mol of VC, 1 mol of NbC, 0.5 mol of Mo2C (providing 1 mol of Mo atoms), and 1 mol of WC were weighed. The total molar amount of carbon in the above formula is: 1(TiC) + 1(VC) + 1(NbC) + 0.5(Mo2C) + 1(WC) = 4.5 mol. The total molar ratio of carbon to transition metal is 4.5 / 5 = 0.900, meaning the nominal composition of the system is (TiC + V) + VC + 1(NbC) + 0.5(Mo2C) + 1(WC) = 4.5 mol. 0.2 V 0.2 Nb 0.2 Mo 0.2 W 0.2 C 1-xThe carbon sublattice vacancy concentration x = 0.100. Deionized water, polyether F127 (2.92% of the carbide powder mass), sodium carboxymethyl cellulose (1% of the carbide powder mass), and BYK-028 defoamer (0.2% of the carbide powder mass) were mixed and added to a zirconia ball mill jar. The mixture was ball-milled at a ball-to-powder mass ratio of 3:1 and a ball milling speed of 1200 rpm for 1 h to prepare a mixed carbide slurry with a solid volume fraction of 41 vol%.
[0056] S2 direct writing modeling:
[0057] The printing parameters are the same as in Example 1. After printing, a mixed carbide precursor preform is obtained.
[0058] S3 Ultrafast In-situ High-Entropy Sintering:
[0059] The drying and degreasing processes were the same as in Example 1. During the high-entropy sintering stage, the in-situ solid solution reaction was completed under vacuum conditions by heating to 2200 °C at a rate of 500 °C / min and holding for 2 min. After sintering, the temperature was cooled to room temperature at a rate of 400 °C / min. The average linear shrinkage rate of the skeleton was 10.8%.
[0060] Reference Figure 8 X-ray diffraction analysis confirmed that the obtained framework was a single-phase face-centered cubic rock salt type (Ti0.2V0.2Nb0.2Mo0.2W0.2)C. 1-x High-entropy carbides.
[0061] S4 Vacuum Pressureless Copper Impregnation:
[0062] The impregnation parameters were adjusted as follows: temperature was increased to 300℃ at 5℃ / min and held for 10 min; then increased to 1000℃ at 10℃ / min and held for 10 min; finally, the temperature was increased to 1200℃ at 5℃ / min and held for 3 min, followed by cooling to room temperature at 10℃ / min. This yielded Cu-(Ti) 0.2 V 0.2 Nb 0.2 Mo 0.2 W 0.2 C 1-x Composite material. The composite material has a density of 99.5%. The volume fraction of the ceramic phase is approximately 32%.
[0063] Example 3 Cu-(Ti) 1 / 7 V 1 / 7 Nb 1 / 7 Ta 1 / 7 Cr 1 / 7 Mo 1 / 7 W 1 / 7 C 1-x Preparation of composite materials
[0064] S1 Slurry Preparation:
[0065] TiC, VC, NbC, TaC, Cr3C2, Mo2C, and WC were used as carbide precursor powders with a FSSS particle size of 0.2–3 μm. Each carbide powder was weighed according to an equimolar ratio (1:1:1:1:1:1:1) of Ti, V, Nb, Ta, Cr, Mo, and W atoms. The specific batching calculations are as follows: Assuming a total transition metal molar amount of 7 mol (1 mol of each element), then 1 mol of TiC, 1 mol of VC, 1 mol of NbC, 1 mol of TaC, 1 / 3 mol of Cr3C2 (providing 1 mol of Cr atoms), 0.5 mol of Mo2C (providing 1 mol of Mo atoms), and 1 mol of WC were weighed. The total molar amount of carbon in the above ingredients is: 1(TiC) + 1(VC) + 1(NbC) + 1(TaC) + 1 / 3(Cr3C2) + 0.5(Mo2C) + 1(WC) = 6.167 mol. The total molar ratio of carbon to transition metals is 6.167 / 7 = 0.881, meaning the nominal composition of the system is (TiC + VC + Cr2C) + Cr3C2 + Cr2C + Cr3C2 ... 1 / 7 V 1 / 7 Nb 1 / 7 Ta 1 / 7 Cr 1 / 7 Mo 1 / 7 W 1 / 7 C 0.881 The carbon sublattice vacancy concentration x≈0.119. Deionized water, polyether F127 (4.8% of the carbide powder mass), sodium carboxymethyl cellulose (0.5% of the carbide powder mass), and BYK-028 defoamer (0.1% of the carbide powder mass) were mixed and added to a zirconia ball mill jar. The mixture was ball-milled at a ball-to-powder mass ratio of 3:1 and a ball milling speed of 1200 rpm for 1 h to prepare a mixed carbide slurry with a solid volume fraction of 30 vol%.
[0066] S2 direct writing modeling:
[0067] The printing parameters are the same as in Example 1. After printing, a mixed carbide precursor preform is obtained.
[0068] S3 Ultrafast In-situ High-Entropy Sintering:
[0069] The drying and degreasing processes were the same as in Example 1. During the high-entropy sintering stage, argon gas was introduced to 0.5 atmospheres, and the temperature was increased to 2300℃ at 400℃ / min and held for 3 min to complete the in-situ solid solution reaction. After sintering, the temperature was cooled to room temperature at 400℃ / min. The average linear shrinkage rate of the skeleton was 11.2%.
[0070] Reference Figure 8X-ray diffraction analysis confirmed that the obtained framework was a single-phase face-centered cubic rock salt type (Ti1 / 7V1 / 7Nb1 / 7Ta1 / 7Cr1 / 7Mo1 / 7W1 / 7)C 1-x High-entropy carbides.
[0071] S4 Vacuum Pressureless Copper Impregnation:
[0072] Reference Figure 6 Cu exhibits excellent wettability with this 7-component high-entropy ceramic substrate. The impregnation process is the same as in Example 1, ultimately yielding Cu-(Ti) 1 / 7 V 1 / 7 Nb 1 / 7 Ta 1 / 7 Cr 1 / 7 Mo 1 / 7 W 1 / 7 C 1-x Composite material. The composite material has a density of 99.1%. The volume fraction of the ceramic phase is approximately 22%.
[0073] Example 4 Cu-(Ti) 0.2 V 0.2 Nb 0.2 Ta 0.2 Mo 0.2 C 1-x Preparation of composite materials
[0074] S1 Slurry Preparation
[0075] TiC, VC, NbC, TaC, and Mo2C were used as carbide precursor powders, with FSSS particle sizes ranging from 0.2 to 3 μm. Each carbide powder was weighed according to an equimolar ratio (1:1:1:1:1) of Ti, V, Nb, Ta, and Mo atoms. The specific batching calculations are as follows: Assuming a total transition metal molar amount of 5 mol, then 1 mol of TiC, 1 mol of VC, 1 mol of NbC, 1 mol of TaC, and 0.5 mol of Mo2C (providing 1 mol of Mo atoms) were weighed. The total carbon molar amount was 1 + 1 + 1 + 1 + 0.5 = 4.5 mol, and the total molar ratio of carbon to transition metals was 0.900, meaning the nominal composition of the system was (Ti... 0.2 V 0.2 Nb 0.2 Ta 0.2 Mo 0.2 C 0.900 Deionized water, xanthan gum (0.5% of the carbide powder mass), sodium carboxymethyl cellulose (2% of the carbide powder mass), and BYK defoamer (0.15% of the carbide powder mass) were mixed and added to a ball mill jar. The mixture was ball-milled at a ball-to-powder ratio of 3:1 and a speed of 800 rpm for 2 hours to prepare a mixed carbide slurry with a solid volume fraction of 50 vol%.
[0076] S2 Direct Writing:
[0077] The printing parameters were adjusted as follows: nozzle diameter 1mm, layer height 0.8mm, printing speed 10mm / s, extrusion pressure 0.6MPa, and concentric circle internal filling with a ring spacing of 0.5mm. A mixed carbide precursor preform was obtained after printing.
[0078] S3 Ultra-fast In-situ High-Entropy Sintering:
[0079] After the printed preform was allowed to air dry at room temperature, it was placed in an ultra-fast sintering apparatus. The furnace chamber was evacuated to 5.0 Pa, and during the degreasing stage, the temperature was increased to 500 °C at 100 °C / min and held for 5 min. Subsequently, under vacuum conditions, the temperature was increased to 1900 °C at 400 °C / min and held for 5 min. After sintering, it was cooled to room temperature at 200 °C / min. The average linear shrinkage rate of the skeleton was 11.5%. (Reference) Figure 8 X-ray diffraction analysis confirmed that the obtained framework was a single-phase face-centered cubic rock salt type (Ti). 0.2 V 0.2 Nb 0.2 Ta 0.2 Mo 0.2 C 1-x High-entropy carbides.
[0080] S4 Vacuum Pressureless Copper Impregnation:
[0081] The impregnation process was adjusted as follows: the temperature was increased to 300℃ at a rate of 5℃ / min and held for 10 min; then increased to 1000℃ at a rate of 10℃ / min and held for 10 min; finally, the temperature was increased to 1150℃ at a rate of 5℃ / min and held for 5 min, followed by a decrease to room temperature at a rate of 10℃ / min. This yielded Cu-(Ti) 0.2 V 0.2 Nb 0.2 Ta 0.2 Mo 0.2 C 1-x Composite material. The composite material has a density of 99%, and the volume fraction of the ceramic phase is approximately 40%.
[0082] Example 5 Cu-(Ti) 0.2 V 0.2 Nb 0.2 Ta 0.2 W 0.2 C 1-x Preparation of composite materials
[0083] S1 Slurry Preparation:
[0084] TiC, VC, NbC, TaC, and WC were used as carbide precursor powders. They were weighed according to the equimolar ratio of Ti, V, Nb, Ta, and W atoms. The total molar amount of carbon was 1 + 1 + 1 + 1 + 1 = 5 mol, and the total molar ratio of carbon to transition metals was 1.0, meaning the nominal composition of the system was (Ti... 0.2 V 0.2 Nb 0.2 Ta 0.2 W 0.2 C, x=0. Deionized water, polyether F127 (2% of powder mass), sodium carboxymethyl cellulose (1.8% of powder mass), and BYK defoamer (0.8% of powder mass) were mixed and ball-milled at 1500 rpm for 0.5 h to prepare a slurry with a solid volume fraction of 40 vol%.
[0085] S2 Direct Writing:
[0086] Printing parameters: nozzle diameter 0.5 mm, layer height 0.4 mm, printing speed 2 mm / s, extrusion pressure 0.1 MPa, filling method is zigzag, line spacing is 0.3 mm.
[0087] S3 Ultra-fast In-situ High-Entropy Sintering:
[0088] The drying process was the same as in Example 1. The dried green body was placed in an ultra-fast sintering apparatus, and the furnace cavity was evacuated to 5.0 Pa. During the degreasing stage, the temperature was increased to 700℃ at 300℃ / min and held for 1 min. Subsequently, the temperature was increased to 2200℃ at 1000℃ / min and held for 1 min. The average linear shrinkage rate of the skeleton was 9.5%. (Refer to...) Figure 8 X-ray diffraction analysis confirmed that the obtained framework was a single-phase face-centered cubic rock salt type (Ti). 0.2 V 0.2 Nb 0.2 Ta 0.2 W 0.2 C 1-x High-entropy carbides.
[0089] S4 Vacuum Pressureless Copper Impregnation:
[0090] The impregnation process was the same as in Example 1. The final composite material had a density of 99% and a ceramic phase volume fraction of approximately 35%.
[0091] Example 6 Cu-(Ti) 1 / 6 V 1 / 6 Nb 1 / 6 Ta 1 / 6 Cr 1 / 6 Mo 1 / 6 C 1-x Preparation of composite materials
[0092] S1 Slurry Preparation:
[0093] TiC, VC, NbC, TaC, Cr3C2, and Mo2C were used as raw materials. The materials were weighed according to the equimolar ratio of Ti, V, Nb, Ta, Cr, and Mo (1:1:1:1:1:1), assuming a total molar amount of 6 mol of transition metals. The total molar amount of carbon was 1 + 1 + 1 + 1 + 2 / 3 + 0.5 = 5.167 mol, and the total molar ratio of carbon to transition metals was 0.861, i.e., the nominal composition was (TiC, VC, NbC, TaC, Cr3C2, and Mo2C). 1 / 6 V 1 / 6 Nb 1 / 6 Ta 1 / 6 Cr 1 / 6 Mo 1 / 6 C 0.861 The binder is polyether F127 (4.8% of the powder mass), the dispersant is sodium carboxymethyl cellulose (0.5% of the powder mass) and the defoamer is BYK-028 (0.1% of the carbide powder mass), and a slurry with a solid volume fraction of 40 vol% is prepared.
[0094] S2 Direct Writing:
[0095] The printing parameters are as follows: nozzle diameter 0.2 mm, layer height 0.15 mm, printing speed 5 mm / s, extrusion pressure 0.4 MPa, filling method is linear, and interlayer spacing is 0.2 mm.
[0096] S3 Ultra-fast In-situ High-Entropy Sintering:
[0097] The drying and degreasing process was the same as in Example 1. Argon gas was then introduced to 0.5 atmospheres, and the temperature was increased to 2100°C at a rate of 500°C / min and held for 3 minutes. The average linear shrinkage of the skeleton was 11.6%, as per reference... Figure 8 X-ray diffraction analysis confirmed that the obtained framework was a single-phase face-centered cubic rock salt type (Ti). 1 / 6 V 1 / 6 Nb 1 / 6 Ta 1 / 6 Cr 1 / 6 Mo 1 / 6 C 1-x High-entropy carbides.
[0098] S4 Vacuum Pressureless Copper Impregnation:
[0099] Reference Figure 6 The wetting test curve shows that 1100 o Copper C exhibits excellent wettability with this hexa-eighths high-entropy substrate. The impregnation process is the same as in Example 1. The final composite material has a density of 99.3% and a ceramic phase volume fraction of approximately 35%.
[0100] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification.
Claims
1. A method for preparing a Cu-high-entropy carbide composite material, characterized in that, Includes the following steps: S1: Mix at least five single-component transition metal carbide powders, dispersants, binders and defoamers to prepare a mixed carbide slurry with shear-thinning properties; S2: The mixed carbide slurry is printed using a direct ink writing method to obtain a mixed carbide precursor preform; S3: The mixed carbide precursor green body is subjected to ultra-fast sintering to cause in-situ solid solution reaction of each component transition metal carbide, resulting in a high-entropy carbide framework with a single-phase face-centered cubic rock salt structure; the heating rate of the ultra-fast sintering is 400-1000℃ / min, the sintering temperature is 1900-2300℃, and the holding time is 1-5min. S4: Under vacuum conditions, metallic copper is heated to melt, and the molten copper is infiltrated into the pores of the high-entropy carbide framework through pressureless capillary infiltration. After cooling, Cu-high-entropy carbide composite material is obtained.
2. The preparation method according to claim 1, characterized in that, The single-component transition metal carbide powder described in S1 is selected from at least five of TiC, VC, NbC, TaC, Cr3C2, Mo2C and WC. The FSSS particle size of the powder is 0.2 to 3 μm, and the proportion of each carbide powder is weighed according to the equimolar ratio or near equimolar ratio of transition metal atoms.
3. The preparation method according to claim 1, characterized in that, The solid volume fraction of the mixed carbide slurry in S1 is 30-50 vol%, the binder accounts for 0.5-5% of the mass of the carbide powder, the binder is polyether F127 or xanthan gum, the dispersant accounts for 0.5-2% of the mass of the carbide powder, and the dispersant is sodium carboxymethyl cellulose.
4. The preparation method according to claim 1, characterized in that, The printing parameters for direct ink writing described in S2 are: nozzle orifice diameter 0.2–1.0 mm, layer height 0.15–0.8 mm, printing speed 2–10 mm / s, extrusion pressure 0.1–0.6 MPa, and filling method is linear, concentric circle, or zigzag.
5. The preparation method according to claim 1, characterized in that, The ultra-fast high-temperature sintering described in S3 is carried out under vacuum or inert atmosphere. Before heating to the target temperature, the temperature is first raised to 500-700℃ in vacuum at 100-300℃ / min and held for 1-5min for degreasing treatment.
6. The preparation method according to claim 1, characterized in that, The average linear shrinkage rate of the high-entropy carbide framework described in S3 is 9.5–12.5%, and the general formula of the high-entropy carbide framework is (A1A2…A…). n C 1-x A1 to A n Each element is independently selected from one of Ti, V, Nb, Ta, Cr, Mo, and W, and any five or more elements coexist in the same metal sublattice, n≥5; x represents the carbon sublattice vacancy concentration, and 0≤x≤0.
15.
7. The preparation method according to claim 1, characterized in that, The pressureless capillary impregnation temperature described in S4 is 1100–1200℃, the holding time is 3–10 min, and the vacuum degree is ≤1×10⁻⁶. -3 Pa.
8. A Cu-high-entropy carbide composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.
9. The Cu-high entropy carbide composite material according to claim 8, characterized in that, The composite material consists of a high-entropy carbide ceramic phase and a metallic copper phase. The high-entropy carbide ceramic phase has a single-phase face-centered cubic rock salt structure with the general formula (A1A2…A…). n C 1-x A1 to A n Each is independently selected from one of Ti, V, Nb, Ta, Cr, Mo, and W, where n ≥ 5 and 0 ≤ x ≤ 0.
15.
10. The Cu-high entropy carbide composite material according to claim 8, characterized in that, The composite material has a density of 99-99.5%, a volume fraction of 20-40% for the high-entropy carbide ceramic phase, and a porosity of less than 1%.